Gambaran Alasan Penggunaan Lensa Kontak pada Mahasiswa Fakultas Kedokteran - Ryanaldi Bagy; Wenny P. Supit; Rillya D. P. Manoppo (Medical Scope Journal, 2024)
Abstract: Despite being aware of the complications associated with contact lens and the practice of hygienic contact lens wear, many medical faculty students still wear contact lenses. This study aimed to obtain the reasons of contact lens wear among medical faculty students. This was a quantitative and descriptive study with a cross-sectional design conducted through total sampling. Respondents were students at Medical Faculty of Universitas Sam Ratulangi that wore contact lens. A total of 83 respondents participated in this study. Based on age groups, there was a tendency for differences in reasons related to ease of access. Based on gender, there was a tendency for differences in cosmetic reasons and the perception that wearing contact lenses were more comfortable than glasses. Overall, the reasons for the respondents to use contact lenses revolved around correction of refractive disorders, cosmetic purposes, and as a substitute for glasses. In conclusion, respondents' reasons for wearing contact lenses tend to be related to correcting refractive disorders, cosmetic purposes, and as a substitute for glasses. Keywords: reasons; contact lens wearers; medical faculty students    Abstrak: Jumlah mahasiswa fakultas kedokteran yang menggunakan lensa kontak relatif banyak walaupun mahasiswa telah mengetahui komplikasi penggunaan lensa kontak dan praktik penggunaan lensa kontak yang higenis. Penelitian ini bertujuan untuk mendapatkan alasan penggunaan lensa kontak pada mahasiswa fakultas kedokteran. Jenis penelitian ialah kuantitatif yang bersifat deskriptif dengan desain potong lintang. Sampel penelitian diperoleh dengan total sampling. Responden penelitian ialah mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi (FK Unsrat) yang menggunakan lensa kontak. Hasil penelitian mendapatkan 83 mahasiswa FK Unsrat sebagai responden penelitian. Berdasarkan kelompok usia, terdapat kecenderungan perbedaan pada alasan kemudahan akses. Berdasarkan jenis kelamin, terdapat kecenderungan perbedaan pada alasan kosmetik dan alasan lensa kontak lebih nyaman daripada kacamata. Secara keseluruhan, alasan mahasiswa FK Unsrat untuk menggunakan lensa kontak cenderung pada alasan untuk mengoreksi gangguan refraksi, kosmetik, dan sebagai pengganti kacamata. Simpulan penelitian ini ialah alasan responden untuk menggunakan lensa kontak cenderung untuk mengoreksi gangguan refraksi, kosmetik, dan sebagai pengganti kacamata. Kata kunci: alasan; pengguna lensa kontak; mahasiswa fakultas kedokteran